PENGARUH PENGHEMATAN PUPUK BUATAN MELALUI PENGGUNAAN PUPUK ORGANIK TERHADAP PRODUKTIVITAS PADI (Oryza sativa L.) PADA SISTEM TANAM SRI - Jamilah .; Samsul Bahri; Milda Ernita (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2010)
ABSTRACT The study of influence organic manure to save the fertilizer to get yield of rice (Oriza sativa L.) at system plant SRI have been conducted at paddy soil at Manggindo Jorong Sangkir Kenagarian Lubuk Basung Province West Sumatra in the year 2009. Target was to get measuring fertilize able to be economized by using organic manure to increase result of rice field paddy in conducting of SRI. Attempt used Complete Random Design (RAL), with treatment of comparison of thrift of usage of fertilizer with addition of organic manure 6 treatment and 4 times restating, so that there were 24 attempt plot. As for fertilizer and organic manure which used in this research [is] : 200 kg/ ha Urea, 100 kg / ha SP-36, 50 kg / ha MOP and 10.000 Sink / ha Compost hay + cage manure ( v / v). The treatment [is] : 100% Manure Made in without organic manure ( A); 100% manure made in + 100% organic manure ( B); 75% manure made in + 100% organic manure ( C); 50% manure made in + 100% organic manure ( D); 25% manure made in + 100% organic manure ( E); and 100% organic manure without manure made in ( F). Data of Disidikragam, if F [count/calculate] bigger than real F level 5% continued with Test of Duncan New Method of Range Test ( DNMRT) [at] real level 5% by using program of SPSS 15. Perception for example is a. High [of] crop, Amount of anakan per clump, Amount of productive anakan per clump, Amount of productive anakan, length of Malai, Amount of shell of rice per malai,. Amount of shell of rice of bernas per malai, wight 1000 seed, dry Production shell of rice per plot and per hectare. Best result obtained from treatment with [gift/ giving] of manure made in 100% with organic manure 100% with production rate of gabak dry equal to 5, 05 ton / Ha. Boundary thrift of usage of manure made in with addition of organic manure able to be lenient by paddy of IR42 to obtain;get result of maximal [at] this research [is] treatment that is 25% manure made in + 100% organic manure. Key words: SRI, organic manure, saving fertilizer